High dose dexamethasone increases circulating P-selectin and von Willebrand factor levels in healthy men - Jilma, Bernd; Cvitko, Tuende; Winter-Fabry, Astrid; Petroczi, Karin; Quehenberger, Peter; Blann, Andrew D. (Thrombosis and Haemostasis, 2005)
Although glucocorticoids are widely used in a number of inflammatory disorders associated with endothelial and platelet activation, their effect on the endothelium and platelets in humans remain poorly defined. Hence, we measured changes of a specific endothelial cell marker (von Willebrand factor [vWF]) and of a platelet marker (soluble P-selectin) by infusing therapeutic doses of dexamethasone (0.04 mg/kg and 1.0 mg/kg b.i.d on two days) or placebo into nine healthy men. Venous citrated plasma was obtained before infusion, and at 24 and 48 h. Compared to baseline levels, we found increased levels of vWF at both time points at the higher dose (p=0.011). Plasma levels of sP-selectin rose at 48 h after the high dose (p=0.017). Human umbilical endothelial cells were cultured in the presence or absence of de-xamethasone (0, 0.01, 1 μM), to determine the possible mechanism for the increase in vWF. The vWF-mRNA levels as quantified by RT-PCR increased 2-fold (p<0.05), and the vWF-concentrations in cell lysates increased by 38% (p<0.05), whereas the vWF-concentrations in the supernatants were unaffected. In summary, high dose DEXA increases sP-selectin and vWF. The probable underlying mechanism for the latter was a DEXA induced up-regulation of vWF-mRNA transcription. Together, this indicates that high dose glucocorticoids may enhance haemostasis, which could be beneficial under certain conditions, but which may also contribute to adverse vascular events by increasing platelet activation and vWF dependent thrombosis.
Keywords: Von Willebrand factor; P-selectin; dexamethason; randomised controlled trial